The impact of switching costs on closing of service branches - Mira G. Baron (European Regional Science Association (ERSA), 2002)
The paper deals with the optimal location of service branches. Consumers can receive service from different firms and branches offering substitute services. The consumer chooses the firm and the branch. Examples are banking services (which firm and branch?), healthcare providers, insurance companies and their agents, brokerage firms and their branches. With the change in the accessibility of the internet, the service industry witnesses the impact of the change in technology. More customers prefer acquiring services over the internet, and less require face to face contacts. The industry has to respond in limiting the number of branches. The paper deals with the question which branches to close. In the first period, each consumer selects to receive service from the branch that minimizes the overall costs incurred, composed of price per service plus transportation costs. In the second period, the branches' configuration changes. A branch is closed by one of the firms in alternative locations. When a consumer wants to switch firms, he incurs additional costs, "exogenous switching costs", the cost of information, learning costs transaction costs. These costs are incurred by the consumers, and are different from "endogenous switching costs" that are incurred by the firm, e.g., the frequent flier case. The paper investigates how the market area and market share of the branches and firms change with the closure of a branch. The loss varies between no loss to losing the whole market. Given the prices, the switching costs and the location, we identify the branches to be closed.
Keywords: 330